2003
DOI: 10.1111/1467-9450.00354
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in children's emotion understanding: Effects of age and language

Abstract: Over the last two decades, it has been established that children's emotion understanding changes as they develop. Recent studies have also begun to address individual differences in children's emotion understanding. The first goal of this study was to examine the development of these individual differences across a wide age range with a test assessing nine different components of emotion understanding. The second goal was to examine the relation between language ability and individual differences in emotion un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
199
1
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(234 citation statements)
references
References 31 publications
14
199
1
20
Order By: Relevance
“…Showing a firm, and perhaps causal, link between emotion understanding and language development, Cutting and Dunn (1999) found that preschoolers' language abilities, including both receptive and expressive language, were correlated with their emotion understanding as indicated by their ability to label and predicts others' affects. Further, Pons, Lawson, Harris, and deRosney (2003) showed that age and language ability together explain most (70%) individual differences in development of emotion understanding in children followed between 4 and 11 years of age. These findings suggest that children's understanding of emotions may be partially dependent upon their language abilities.…”
Section: Young Children's Understanding Of Emotionsmentioning
confidence: 98%
“…Showing a firm, and perhaps causal, link between emotion understanding and language development, Cutting and Dunn (1999) found that preschoolers' language abilities, including both receptive and expressive language, were correlated with their emotion understanding as indicated by their ability to label and predicts others' affects. Further, Pons, Lawson, Harris, and deRosney (2003) showed that age and language ability together explain most (70%) individual differences in development of emotion understanding in children followed between 4 and 11 years of age. These findings suggest that children's understanding of emotions may be partially dependent upon their language abilities.…”
Section: Young Children's Understanding Of Emotionsmentioning
confidence: 98%
“…First, we investigated whether the level of emotion understanding in a sample of 35 preschool children with mild-to-severe hearing loss, fitted with HA, was lower than that in a group of TH children drawn from a representative community sample. Because language is known to be an important predictor of emotion understanding in TH children (Harris et al, 2005;Pons, Lawson, Harris, & De Rosnay, 2003) and DHH children are at risk for language delays , we included vocabulary in our analysis as a control variable to be able to separate the contributions of hearing loss and vocabulary. Second, we examined whether parents of children with HA have different perceptions of their child's level of emotion understanding compared to parents of TH children.…”
Section: The Present Studymentioning
confidence: 99%
“…Son olarak da dil ediniminde öğrenme süreçlerinin, önemsiz olduğundan hareket eder, çünkü ona göre çevrenin dili hep noksan ve kusurludur (Weinert, 2000;Szagun, 2008). Oysa dilsel gelişimin ya da dil edinim sürecinin çevresel ve duygusal faktörlerden bağımsız olarak işlediğini tasavvur etmek pek mümkün değildir (Pons, 2003;Andresen, 2006;Lin-Huber, 2006;Lüdtke, 2012) Yaptığımız araştırmalar intrapsişik süreçlerin, duygulanım düzenlenmesi (affect regulation) ya da duygu (emotion) faktörlerinin dil edinimindeki rolü konusunun nativizmde yer bulmadığı sonucunu doğurmuştur. O'Grady'nin işlemcisi çağrışımlar yaratmak ya da bir sözcükte yatan anlamsal tüm olasılıkları kayıt altına almak ve bunu yeni durumlara uyarlamak ve performe etmek ile hükümlü bir sistem olarak düşünülebilir.…”
Section: Nativist (Doğuştancı) Yaklaşım -Noam Chomskyunclassified
“…Nowadays, most researchers assume that the language acquisition of infants is a progressive process that proceeds in parallel with perceptual, motoric, social-emotional, and cognitive development (Klein 1984;Klann-Delius1999;Datler/Bamberger/Studener 2000;Hennon/HirschPasek/Golinkoff 2000;Pons 2003;Bredel, 2005;Friesel 2007;Zollinger 2010;Lüdtke 2012). Today, many writers from various scientific disciplines move from the fact that not only sociocultural and biological factors, but also emotional elements as motivation, fear, happiness, sadness might have a constitutive role in children's development (Andresen 2006;Datler/Bamberger/Studener 2000, Datler 2013Friesel 2007;Lin-Huber 2006;Lüdtke 2012;Martschinke/Kammermeyer, 2006;Pons 2003;Riemer 2002Riemer , 2004Schwarz-Friesel 2004).…”
Section: Extended English Abstractmentioning
confidence: 99%
See 1 more Smart Citation